Kajian Etnobotani Tanaman Rempah sebagai Bumbu, Obat dan Kias - Siti Nuraeni; Budiawati Supangkat; Johan Iskandar (Umbara, 2022)
Traditional market has been the main provider of various spices and herbs. This research aims to describe spices and herbs being traded in Warungkondang traditional market, West Java. It also aims to describe how people use those spices and herbs for various purposes such as seasonings, traditional medicine, as well as kias (amulet). This research was conducted using a qualitative method, in particular ethnography. Data were collected through participant observation and semi-structured interviews. This research identifies 32 species of spices and herbs being traded in the market. Among those, 21 species  have been used not only for seasonings but also as traditional medicines, and kias. Cikur (Kaempferia galanga), honje (Etlingera elatior), jahe (Zingiber officinale), koneng (Curcuma longa), and laja (Alpinia galanga) are the most widely used spices and herbs. Parents and family members as well as electronic mass media have been the main sources of knowledge about spices and herbs, and its benefit. In Warungkondang market, knowledge about spices and herbs has been exchanged among buyers and sellers. This indicates the crucial role of traditional market which is not only serves as provider of spices and herbs, but also as the place where knowledge about it has been preserved and exchanged.